Acorn flour as a source of bioactive compounds in gluten-free bread - Martins, Rita Beltrão (2020)
Polyphenols are important bioactive compounds whose regular ingestion has shown di erent positive impacts in health. Celiac patients have nutritional deficiencies, bringing many problems to their health. Thus, it is important to develop gluten-free (GF) products, such as bread, with nutritional benefits. The acorn is the fruit of holm oak and cork oak, being an underexploited resource nowadays. Its nutritional and functional characteristics are remarkable: rich in unsaturated fatty acids and fiber, vitamin E, chlorophylls, carotenoids, phenolic compounds, and antioxidant properties. The purpose of this study was to assess the use of acorn flour as a bioactive compounds source and natural GF ingredient for baking GF bread. Bread loaves were prepared with buckwheat, rice, acorn flour, and potato starch. Two levels of acorn flour (23% and 35% of the flour mixture) were tested. The physical, nutritional, and sensory characteristics of the bread were analysed, as well as the composition of phenolic compounds: total phenols, ortho-diphenols, and flavonoids. The phenolic profile was assessed by Reverse Phase–High-Performance Liquid Chromatography–Diode Array Detector (RP-HPLC-DAD). The antioxidant activity of the bread extracts was determined by 2,2-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) diammonium salt (ABTS), diphenyl-1-picrylhidrazyl radical (DPPH), and ferric reducing antioxidant power (FRAP) methodologies. Acorn flour can be considered a good source of bioactive compounds and antioxidants in GF bread. Acorn flour showed good technological properties in GF baking, improving bread nutritional and sensory characteristics